The Effect of Instructional Guidelines on Women that Suffer from Genital Prolapse - Mervat Saad Fathy Saad; Entesar Fatouh Abdel Moniem; Rania Abd El-hak Eid Farrag; Haitham Mohannad Badran (CV. Global Health Science Group, 2021)
Genital prolapse is one of the most frequent causes of gynecological morbidities among women in the world. The symptoms of genital prolapse can be extremely debilitating and have an appreciable impact on quality of life. The present study aimed to evaluate the effect of instructional guidelines on women that suffer from genital prolapse . Quazi experimental design was conducted at the out-patient’s clinics of Fayoum University hospital and General hospital (obstetrics and gynecology clinic). Purposive sample 73 women was included in the study. Data were collected through four types of tools (structured interviewing questionnaire sheet, Pelvic Organ Prolapse Quantification system (POP–Q) . It was used to assess genital prolapse, Pelvic organ prolapse-symptoms score (POP-ss),it was used to assess symptoms of genital prolapse and Instructional guidelines follow up sheet was designed to assess the manifestations. The results of this study revealed that there were a statistically no significant differences between the women with satisfactory level of knowledge and genital prolapsed symptoms, and its stages before instructional guidelines. While the result is almost statistically significant between the women with satisfactory level of knowledge and symptoms and stages after instructional guidelines, there were a statistically significant differences between the genital prolapsed symptoms and its stages before and after instructional guidelines. The study concluded that instructional guidelines was effective in improving women' knowledge and stages regarding genital prolapse. As well a reduction in prolapse symptoms which lead to better quality of life at follow-up periods.